2020
DOI: 10.1111/jcap.12300
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the internalized stigma of Mental Illness Scale–Adolescent Form

Abstract: Purpose The goal of this study was to assess the validity and reliability of the Turkish version of the Internalized Stigma of Mental Illness Scale–Adolescent Form (ISMI‐AF). Methods A total of 145 adolescents (12–18 years of age) who were diagnosed with at least one mental disorder according to DSM‐5‐TR participated in the study. Data were collected at a mental health hospital between October 2017 and 2019 using a sociodemographic information form, the ISMI‐AF, and Beliefs towards Mental Illness (BMI) Scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The total ISMI‐AF points of the adolescents in the current study were determined to be at a moderate level (Table 4). This was similar to the findings of the ISMI‐AF validity and reliability study by Dikeç et al (2021), which showed a moderate level of internalize stigmatization with a mean of 2.06 ± 0.45 points. In the current study, gender and number of hospitalizations explained 18% of the change in the total ISMI‐AF scale points (Table 5).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The total ISMI‐AF points of the adolescents in the current study were determined to be at a moderate level (Table 4). This was similar to the findings of the ISMI‐AF validity and reliability study by Dikeç et al (2021), which showed a moderate level of internalize stigmatization with a mean of 2.06 ± 0.45 points. In the current study, gender and number of hospitalizations explained 18% of the change in the total ISMI‐AF scale points (Table 5).…”
Section: Discussionsupporting
confidence: 90%
“…This form was developed by Boyd‐Ritsher et al (2003) and the reliability and validity studies of the Turkish version were conducted by Dikeç et al (2021). It is a self‐reported scale of 29 items evaluating internalized stigmatization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, two information forms were used to collect data on adolescents' and their parents' socio-demographic status and mental illnesses. There were 11 questions designed for adolescents, which formed the Adolescent Information Form, and there were 13 questions in the Parent Information Form [18,21,[24][25][26][27]. The internalized stigmatization levels of the adolescents were determined by the Internalized Stigmatization of Mental Illness Scale-Adolescents Form (ISMI-AF).…”
Section: Measurementsmentioning
confidence: 99%